Cover Image, Volume 38, Issue 13. (16th December 2018) - Skinner, Sasha; DeKoninck, Philip; Crossley, Kelly; Amberg, Benjamin; Deprest, Jan; Hooper, Stuart; Hodges, Ryan
Abstract : The discoid hemochorial placenta in the humans is diagrammatically represented (left panel), with maternal blood from uterine spiral arteries bathing fetal chorionic villi containing fetal vessels. The sheep cotyledonary synepitheliochorial structure is compared (right panel), with multiple placentomes throughout the uterus. Sasha Skinner et al., in this issue. DOI:https://doi.org/10.1002/pd.5362 . Drawing by Myrthe Boymans, ©UZ Leuven.